ChemInform Abstract: Highly Efficient Modular Metal‐Free Synthesis of 3‐Substituted 2‐Quinolones. Issue 18 (May 2015) - Aksenov, Alexander V.; Smirnov, Alexander N.; Aksenov, Nicolai A.; Aksenova, Inna V.; Bijieva, Asiyat S.; Rubin, Michael
Abstract by a cascade annulation of aryl hydrazines with nitroketones in PPA